A Bio-inspired anti-slipping winter shoe-sole - Richhariya, Vipin (2021)
Hundreds of thousands of people injure every year due to Slips and Falls (SF) around the globe. The SF on ice during wintertime is an inevitable proposition. Though SF injuries don’t seem concerning, it ranks second among the causes of injuries in the world claiming billions of euros and thousands of lives. The staggering outcomes of SF are loss of jobs (for the people getting injured), loss of skilled workers (for the companies which trained the worker), expenses on the healthcare, burden on the insurance companies and social securities. To reduce SF, anti-slipping shoe-soles are used, however, existing soles provide very limited rescue from the slippage. Moreover, existing solution either modify material or tread design to increase friction on the icy surfaces. In this work, nature-inspired anti-slipping winter shoe-soles are being explored that combine material and tread design variation together using Laser Surface Texturing (LST) to obtain higher friction.